2022
DOI: 10.37934/cfdl.14.11.2239
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation Model for Optimum Design of B-Series Propeller using Multiple Reference Frame (MRF)

Abstract: Propulsion system is one of ship systems which require more attention, especially on propeller design. The propeller design greatly affects the ship speed. It is expected to be able to have maximum value of thrust coefficient and efficiency. Hence, the optimum design of propeller can be obtained by multi objective optimization process. In this study, a preliminary optimization is applied to B-series propeller with the Non-dominated Sort Genetic Algorithm-II (NSGA-II). The purpose of this study is to find out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Afterwards they were weighed again after being dried. Analysis of mass loss were conducted by method of ASTM explained previously [33][34][35][36][37][38][39]. The tests were conducted in duplicate in order to assure the results accuracy and the weight loss mean was reported.…”
Section: Weight Loss Analysismentioning
confidence: 99%
“…Afterwards they were weighed again after being dried. Analysis of mass loss were conducted by method of ASTM explained previously [33][34][35][36][37][38][39]. The tests were conducted in duplicate in order to assure the results accuracy and the weight loss mean was reported.…”
Section: Weight Loss Analysismentioning
confidence: 99%
“…In the past, numerical analysis studies were performed in order to reach a comprehensive understanding of the flow past a simple body before applying the method to a more complex geometry. Nowadays, CFD is a more reliable method of analysing the hydrodynamics of a complex geometry such as a ship (both free surface ships and submarines), and many kinds of CFD approaches have been applied (Sugianto et al 2022;Permadi and Sugianto 2022). Atta et al (2019) used CFD to perform a hydrodynamic design and performance analysis of underwater vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental study determined that selecting the right material of manufacture for burner is important for moderating air pollutants from combustion of LPG and enhance air quality greatly. They found that the burners made of cast iron and brass have emission indices which satisfactory standard limit by International Organization for Standardization and other regulations [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%